Biobehavioral Interventions in Headache Treatment - Weeks, Randall E. (Seminars in Neurology, 2022)
Headaches may be highly disabling and can have significant direct and indirect costs for the individual, family, and society. Biobehavioral factors are important variables in the assessment and treatment of headache. As a patient's headache frequency and disability increases, comorbid cognitive and behavioral variables may be important treatment considerations in the comprehensive management. This article will discuss various behavioral factors that the headache practitioner should consider when making a headache diagnosis and formulating a treatment strategy. Biobehavioral interventions (e.g., relaxation training, electromyographic training, thermal biofeedback, mindfulness, and cognitive–behavior therapy) and their efficacy will be described and reviewed, but neuromodulation and noninvasive devices are outside the scope of this article.
Keywords: behavioral treatment for headache; biofeedback; cognitive–behavioral therapy